Adhesive composition and adhesive sheet

The adhesive composition with a specific acrylic copolymer and plasticizer addresses the challenge of varying adhesion strengths and removability issues in pressure-sensitive adhesive sheets, ensuring consistent adhesion and easy removal under varying conditions.

JP7618984B2Active Publication Date: 2025-01-22TOYO INK MFG CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2020145400
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-08-31
Publication Date
2025-01-22
Estimated Expiration
2040-08-31

AI Technical Summary

Technical Problem

Pressure-sensitive adhesive sheets with good adhesion to oily surfaces face issues of increasing adhesive strength over time, leading to residue upon removal, and require improved removability and cohesive strength, especially under high temperature and humidity conditions, with varying adhesion strengths between oil-free and oil-attached surfaces.

Method used

An adhesive composition containing an acrylic copolymer with a specific ratio of dodecyl (meth)acrylate and tridecyl (meth)acrylate, combined with a plasticizer, to maintain consistent adhesive strength and removability, using monomers with carboxyl and hydroxyl groups for crosslinking and improved cohesive strength.

Benefits of technology

The adhesive composition achieves suitable adhesive strength for removable applications, maintains low adhesion strength variation between oil-free and oil-attached surfaces, and ensures removability even under high temperature and humidity conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007618984000001
    Figure 0007618984000001
  • Figure 0007618984000002
    Figure 0007618984000002
Patent Text Reader

Abstract

To provide an adhesive composition and a pressure sensitive adhesive sheet having an adhesive force appropriate for re-peeling purposes, with a smaller difference between adhesive forces to a non-oily surface and an oily surface, having excellent re-peeling properties even after a storage under high temperature and high humidity for a long period of time, and excellent in coagulation power under high temperature.SOLUTION: An adhesive composition includes acrylic copolymer and plasticizer. The acrylic copolymer is copolymer including 10 mass% or more monomer of one or more kinds selected from dodecyl (meth)acrylate and tridecyl (meth)acrylate.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an adhesive composition and an adhesive sheet. [Background technology]

[0002] There are various resin-based adhesives, with acrylic adhesives being the most widely used. Acrylic adhesives have the advantage that basic adhesive properties such as adhesive strength and tack can be easily controlled by adjusting the monomer composition and compatible additives. There has long been a market need for adhesives that can adhere to oil-adhered substrates, but in recent years there has been a demand for adhesives that are easier to use and have higher functionality. Patent Document 1 discloses a pressure-sensitive adhesive sheet for use on an adherend surface having oil thereon, which contains a specific (meth)acrylic copolymer and a tackifier having a softening point exceeding 115° C. The pressure-sensitive adhesive sheet is said to have good adhesive strength to oily surfaces. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-095021 A Summary of the Invention [Problem to be solved by the invention]

[0004] There are cases where a pressure-sensitive adhesive sheet is required to be temporarily attached and then peeled off again. The pressure-sensitive adhesive sheet of Patent Document 1 has good adhesive strength to oily surfaces, but the adhesive strength gradually increases over time, and there is a problem that when the sheet is peeled off after several weeks, adhesive residue remains. Furthermore, there is a further demand for pressure-sensitive adhesive sheets that have good adhesive strength even on an adherend surface that has oil on some parts and no oil on other parts.

[0005] The problem that the present invention aims to solve is to provide an adhesive composition and an adhesive sheet which have adhesive strength suitable for removable applications, have a small difference in adhesive strength between an oil-free surface and an oil-covered surface, and have good removable properties even when stored for long periods under high temperature and high humidity conditions, and further have excellent cohesive strength at high temperatures. [Means for solving the problem]

[0006] The adhesive composition according to the present invention is an adhesive composition containing an acrylic copolymer and a plasticizer, and the acrylic copolymer is a copolymer containing 10 mass% or more of one or more monomers selected from dodecyl (meth)acrylate and tridecyl (meth)acrylate.

[0007] In one embodiment of the above-mentioned pressure-sensitive adhesive composition, the plasticizer comprises an ester compound derived from one or more selected from saturated fatty acids having 12 to 18 carbon atoms, unsaturated fatty acids having 12 to 18 carbon atoms, and epoxidized products of unsaturated fatty acids having 12 to 18 carbon atoms.

[0008] In one embodiment of the pressure-sensitive adhesive composition, the acrylic copolymer contains 80 mass % or more of one or more monomers selected from dodecyl (meth)acrylate and tridecyl (meth)acrylate.

[0009] In one embodiment of the pressure-sensitive adhesive composition, the acrylic copolymer further contains a monomer having a carboxyl group.

[0010] The pressure-sensitive adhesive sheet according to the present invention comprises a substrate and an adhesive layer comprising the pressure-sensitive adhesive composition or a cured product thereof. Effect of the Invention

[0011] The present invention provides an adhesive composition and an adhesive sheet which have adhesive strength suitable for removable applications, have a small difference in adhesive strength between an oil-free surface and an oil-covered surface, and have good removable properties even when stored for long periods under high temperature and high humidity conditions, and further have excellent cohesive strength at high temperatures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The adhesive composition and adhesive sheet according to the present invention will be described in order below. In the present invention, the term "(meth)acrylate" refers to either acrylate or methacrylate, and the term "(meth)acryl" is equivalent thereto. In the present invention, the term "copolymer containing a monomer" means that the copolymer contains the monomer as a polymerization component, and has a structural unit derived from the monomer. The proportion of the monomer in the copolymer is based on the total amount of the monomers constituting the copolymer (100% by mass). In the present invention, the "cured product of the adhesive composition" means that at least a part of the components in the adhesive composition has undergone a crosslinking reaction, and for example, a gel-like product is also included in the cured product. In this specification, an alkyl(meth)acrylate having a linear alkyl group with n carbon atoms may be referred to as a Cn alkyl(meth)acrylate. For example, dodecyl(meth)acrylate may be referred to as a C12 alkyl(meth)acrylate. Here, n is an integer of 1 or more. Furthermore, unless otherwise specified, the symbol "~" indicating a numerical range includes the lower limit and the upper limit.

[0013] [Adhesive composition] The adhesive composition of the present invention (hereinafter also referred to as the present adhesive composition) is an adhesive composition containing an acrylic copolymer and a plasticizer, and the acrylic copolymer is a copolymer containing 10 mass% or more of one or more monomers selected from dodecyl (meth)acrylate and tridecyl (meth)acrylate.

[0014] The present inventors have investigated alkyl (meth)acrylates constituting an acrylic copolymer in order to reduce the difference between the adhesive strength to an oily surface (hereinafter also referred to as an oily surface) and the adhesive strength to a non-oily surface (hereinafter also referred to as a non-oily surface). As a result, when a C11 or lower alkyl (meth)acrylate is used, the adhesive strength to an oily surface tends to be lower than the adhesive strength to a non-oily surface. On the other hand, when a C14 or higher alkyl (meth)acrylate is used, the adhesive strength to a non-oily surface tends to be lower. From this knowledge, the present inventors have found that by selecting a C12-C13 alkyl (meth)acrylate, the difference between the adhesive strength to an oily surface and the adhesive strength to a non-oily surface is reduced, and have completed the present invention by combining an acrylic copolymer containing 10 mass % or more of C12-13 alkyl (meth)acrylate with a plasticizer. That is, the adhesive composition has a small difference in adhesive strength between an oily surface and a non-oily surface, and has good removability. Furthermore, C12-C13 alkyl (meth)acrylate has superior reactivity and productivity during synthesis of an acrylic copolymer compared to C14 or higher alkyl (meth)acrylate, and the residual unreacted monomer in the adhesive composition and adhesive layer is suppressed, thereby obtaining a high-quality adhesive layer. The adhesive composition contains at least an acrylic copolymer and a plasticizer, and may further contain other components as required. Each of these components will be described below in order.

[0015] <Acrylic copolymer> In the present adhesive composition, the acrylic copolymer used is a copolymer containing 10% by mass or more of one or more monomers selected from dodecyl (meth)acrylate and tridecyl (meth)acrylate. By using the acrylic copolymer, an adhesive composition having a small difference between the adhesive strength to an oily surface and the adhesive strength to a non-oily surface can be obtained. The dodecyl group and the tridecyl group in the dodecyl (meth)acrylate and the tridecyl (meth)acrylate are linear alkyl groups. In the acrylic copolymer, the total content of the dodecyl (meth)acrylate and the tridecyl (meth)acrylate may be 10% by mass or more, and from the viewpoint of reducing the difference between the adhesive strength to an oily surface and the adhesive strength to a non-oily surface, it is preferably 30 to 99% by mass, more preferably 50 to 99% by mass, further preferably 70 to 99% by mass, and particularly preferably 90 to 99% by mass. The acrylic copolymer is an acrylic (co)polymer containing one or more monomers selected from dodecyl (meth)acrylate and tridecyl (meth)acrylate, and may be an acrylic copolymer further containing other monomers as necessary. Since dodecyl (meth)acrylate and tridecyl (meth)acrylate have clear structures, the explanation here is omitted, and the other monomers will be explained below.

[0016] (Other Monomers) The other monomer is used to impart various functions to the acrylic copolymer and to adjust the physical properties. The other monomer is a compound having one or more polymerizable groups. Examples of the polymerizable group include a vinyl group, an allyl group, and a (meth)acryloyl group. The number of polymerizable groups in one monomer molecule is preferably 1 to 2, and more preferably 1, from the viewpoints of the adhesion and ease of production of the acrylic copolymer. The other monomer can be appropriately selected from known monomers having one or more polymerizable groups. As the other monomer, a linear or branched alkyl (meth)acrylate having 11 or less carbon atoms, a monomer having a carboxyl group, or a monomer having a hydroxyl group is preferable, and a monomer not classified into these may be further included. From the viewpoint of providing a crosslinking point with the curing agent in the acrylic copolymer, it is preferable to include one or more monomers selected from a monomer having a carboxyl group and a monomer having a hydroxyl group.

[0017] The linear or branched alkyl(meth)acrylate having 11 or less carbon atoms improves the adhesive retention of the present adhesive composition at high temperatures. Examples of linear alkyl(meth)acrylates include methyl(meth)acrylate, ethyl(meth)acrylate, butyl(meth)acrylate, and octyl(meth)acrylate. As the branched alkyl(meth)acrylate, for example, 2-ethylhexyl(meth)acrylate and isobutyl(meth)acrylate are preferable. The linear or branched alkyl(meth)acrylate having 11 or less carbon atoms may be used alone or in combination of two or more. From the viewpoint of holding power at high temperatures, linear or branched alkyl(meth)acrylate having 11 or less carbon atoms is preferred. When using a linear or branched alkyl (meth)acrylate having 11 or less carbon atoms, the proportion of C11 or less alkyl (meth)acrylate in the acrylic copolymer is preferably 0.01 to 84 mass%, more preferably 0.01 to 50 mass%, even more preferably 0.01 to 20 mass%, and particularly preferably 0.01 to 10 mass%, from the viewpoint of reducing the difference in adhesion between an oily surface and an oil-free surface while maintaining cohesive strength at high temperatures.

[0018] Carboxylic monomers are monomers that have one or more carboxyl groups in the molecule. Carboxylic monomers impart high adhesive and cohesive strength to non-oily surfaces and, when combined with a curing agent, also act as crosslinking points with the curing agent. The number of carboxyl groups in one molecule of the carboxyl group-containing monomer is preferably 1 to 3, more preferably 1 or 2, and even more preferably 1, from the viewpoint of the adhesiveness of the adhesive layer. Examples of monomers having a carboxyl group include carboxyalkyl (meth)acrylates such as 2-carboxyethyl (meth)acrylate; (meth)acrylic acid, fumaric acid, maleic acid, maleic anhydride, maleic acid monoalkyl ester, vinyl benzoic acid, etc., among which (meth)acrylic acid is preferred. The monomers having a carboxyl group may be used alone or in combination of two or more. When a monomer having a carboxyl group is used, the proportion of the monomer having a carboxyl group in the acrylic copolymer is preferably 0.01 to 20 mass%, more preferably 0.1 to 10 mass%, and even more preferably 2 to 7 mass%, from the viewpoint of imparting high adhesive strength and cohesive strength to non-oily surfaces while reducing the difference in adhesive strength between oily surfaces and non-oily surfaces.

[0019] The monomer having a hydroxyl group is a monomer having one or more hydroxyl groups in the molecule. When the monomer having a hydroxyl group is combined with a curing agent, it also serves as a crosslinking point with the curing agent. The hydroxyl group may be either an alcoholic hydroxyl group or a phenolic hydroxyl group. The number of hydroxyl groups in one molecule of the hydroxyl group-containing monomer is preferably 1 to 3, more preferably 1 or 2, and even more preferably 1, from the viewpoint of the adhesiveness of the adhesive layer. Specific examples of the monomer having a hydroxyl group include hydroxyalkyl (meth)acrylates such as 2-hydroxyethyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, and 8-hydroxyoctyl (meth)acrylate, and among these, 2-hydroxyethyl (meth)acrylate is preferred. The monomer having a hydroxyl group may be used alone or in combination of two or more. When a monomer having a hydroxyl group is used, the proportion of the monomer having a hydroxyl group in the acrylic copolymer is preferably 0.01 to 15 mass%, more preferably 0.05 to 10 mass%, and even more preferably 0.1 to 5 mass%, in order to reduce the difference in adhesive strength between an oily surface and a non-oily surface.

[0020] Furthermore, the acrylic copolymer may contain a monomer that is not classified into the above monomers, such as alkoxyalkyl (meth)acrylates such as methoxymethyl (meth)acrylate, 2-methoxyethyl (meth)acrylate, 3-methoxypropyl (meth)acrylate, 3-ethoxypropyl (meth)acrylate, 4-methoxybutyl (meth)acrylate, and 4-ethoxybutyl (meth)acrylate; Aminoalkyl (meth)acrylates such as aminomethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, N,N-diethylaminoethyl (meth)acrylate, and N,N-dimethylaminopropyl (meth)acrylate; Monomers having an amide group, such as (meth)acrylamide, N-methylol (meth)acrylamide, N,N-dimethyl (meth)acrylamide, diacetone (meth)acrylamide, N-vinylacetamide, N-vinylpyrrolidone, and 4-acryloylmorpholine; Examples of the monomer include vinyl acetate, acrylonitrile, styrene, glycidyl (meth)acrylate, etc. These monomers may be used alone or in combination of two or more.

[0021] The weight average molecular weight of the acrylic copolymer is preferably 300,000 or more, more preferably 500,000 or more, from the viewpoint of obtaining good removability. Also, the weight average molecular weight of the acrylic copolymer is preferably 2,500,000 or less, more preferably 2,000,000 or less, and even more preferably 1,500,000 or less, from the viewpoint of obtaining an adhesive composition having a small difference between the adhesive strength to an oily surface and the adhesive strength to a non-oily surface. In the present invention, the weight average molecular weight is a value calculated in terms of polystyrene measured by gel permeation chromatography (GPC).

[0022] When the acrylic copolymer contains two or more kinds of monomers, the order of bonding is not particularly limited, and the copolymer may be in any form such as a random copolymer, a block copolymer, an alternating copolymer, etc. From the viewpoint of ease of production, a random copolymer is preferred.

[0023] (Method of producing acrylic copolymer) The method for producing the acrylic copolymer may be appropriately selected from known polymerization methods, taking into consideration the order of monomer bonding, etc. For example, in the case of a random copolymer, one or more monomers selected from dodecyl (meth)acrylate and tridecyl (meth)acrylate, and other monomers as necessary, are mixed, and an initiator is further added, and polymerization can be carried out by known polymerization methods such as solution polymerization, bulk polymerization, and various radical polymerizations. Among them, solution polymerization is preferred because it is easy to adjust the weight average molecular weight of the copolymer.

[0024] Specifically, a solvent, a monomer, a polymerization initiator, and the like are generally heated to a reaction temperature of about 50 to 90° C. in an atmosphere of an inert gas such as nitrogen gas, and the polymerization reaction is carried out for 4 to 12 hours.

[0025] Examples of the polymerization initiator include an azo-based initiator and a peroxide-based initiator. These polymerization initiators are usually used in an amount of 0.01 to 5 parts by mass relative to 100 parts by mass of the raw material monomer. In addition, a chain transfer agent, raw material monomer, and solvent may be added appropriately during the polymerization reaction.

[0026] Among the above-mentioned polymerization initiators, examples of the azo-based compounds include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), 2,2'-azobis(2,4-dimethyl-4-methoxyvaleronitrile), dimethyl 2,2'-azobis(2-methylpropionate), 4,4'-azobis(4-cyanovaleric acid), 2,2'-azobis(2-hydroxymethylpropionitrile), and 2,2'-azobis[2-(2-imidazolin-2-yl)propane].

[0027] Among the above-mentioned polymerization initiators, examples of organic peroxides include benzoyl peroxide, t-butyl perbenzoate, cumene hydroperoxide, diisopropyl peroxydicarbonate, di-n-propyl peroxydicarbonate, di(2-ethoxyethyl)peroxydicarbonate, t-butyl peroxyneodecanoate, t-butyl peroxypivalate, (3,5,5-trimethylhexanoyl)peroxide, dipropionyl peroxide, and diacetyl peroxide.

[0028] Under the above conditions, the weight average molecular weight of the resulting copolymer can be adjusted according to known techniques by adjusting reaction conditions such as the type and amount of the solvent used, the type and amount of the polymerization initiator, the reaction time, the reaction temperature, etc.

[0029] <Plasticizer> The adhesive composition contains a plasticizer. A plasticizer is added to materials such as resins to impart flexibility and improve processability. By using a plasticizer in the adhesive composition, it is possible to impart removability while maintaining adhesive strength to an oily surface.

[0030] Examples of the plasticizer include monoesters, diesters, and triesters of monobasic acids or polybasic acids having 1 to 18 carbon atoms and alcohols having 20 or less carbon atoms; esters of saturated fatty acids having 12 to 18 carbon atoms or unsaturated fatty acids having 12 to 18 carbon atoms and tetrahydric or less alcohols; esters of monobasic acids or polybasic acids having 1 to 18 carbon atoms and polyalkylene glycols; diesters, triesters, and tetraesters of hydroxy acids and monobasic acids or alcohols; fatty acid esters in which the unsaturated site has been epoxidized with a peroxide or the like; and phosphate esters.

[0031] Examples of esters of monobasic acids or polybasic acids having 1 to 18 carbon atoms and alcohols having 20 or less carbon atoms include isostearyl laurate, isopropyl myristate, isocetyl myristate, octyldodecyl myristate, isostearyl palmitate, isocetyl stearate, octyldodecyl oleate, diisostearyl adipate, diisocetyl sebacate, trioleyl trimellitate, and triisocetyl trimellitate.

[0032] Examples of the saturated fatty acid having 12 to 18 carbon atoms or the unsaturated fatty acid having 12 to 18 carbon atoms and the tetravalent or less alcohol constituting the ester of the saturated fatty acid having 12 to 18 carbon atoms or the unsaturated fatty acid having 12 to 18 carbon atoms and the tetravalent or less alcohol are as follows. Examples of the saturated fatty acid having 12 to 18 carbon atoms or the unsaturated fatty acid having 12 to 18 carbon atoms include lauric acid, myristic acid, palmitic acid, stearic acid, isopalmitic acid, isostearic acid, myristoleic acid, oleic acid, linoleic acid, linolenic acid, etc. Examples of the tetravalent or less alcohol include ethylene glycol, propylene glycol, glycerin, trimethylolpropane, pentaerythritol, sorbitan, etc.

[0033] Examples of esters of monobasic acids or polybasic acids having 1 to 18 carbon atoms with polyalkylene glycols include polyethylene glycol dihexylate, polyethylene glycol di-2-ethylhexylate, polyethylene glycol dilaurate, polyethylene glycol dioleate, and dipolyethylene glycol methyl ether adipate.

[0034] Examples of esters of hydroxy acids and monobasic acids or alcohols include octyldodecyl lactate, diisostearyl malate, methyl 2-hydroxymyristate, 2-ethylhexyl 12-hydroxystearate, ethyl ricinoleate, methyl o-acetylricinoleate, butyl o-acetylricinoleate, triethyl citrate, tributyl o-acetylcitrate, and tri(2-ethylhexyl) o-acetylcitrate.

[0035] Examples of fatty acid esters in which the unsaturated site is epoxidized with a peroxide or the like include epoxidized oils and fats such as epoxidized soybean oil, epoxidized linseed oil, and epoxidized cottonseed oil, and ester compounds of epoxidized compounds of unsaturated fatty acids having 8 to 18 carbon atoms and linear or branched alcohols having 1 to 6 carbon atoms.

[0036] Examples of the phosphate ester include ester compounds of phosphorous acid or phosphoric acid with a linear or branched alcohol having a carbon number of 2 to 18. Examples include tributyl phosphate, 2-ethylhexyl acid phosphate, oleyl acid phosphate, and ethylene glycol acid phosphate.

[0037] Among these, the plasticizer in the present pressure-sensitive adhesive composition preferably contains an ester compound derived from one or more selected from saturated fatty acids having 12 to 18 carbon atoms, unsaturated fatty acids having 12 to 18 carbon atoms, and epoxidized products of unsaturated fatty acids having 12 to 18 carbon atoms, and among these, an ester compound of one or more selected from saturated fatty acids having 12 to 18 carbon atoms, unsaturated fatty acids having 12 to 18 carbon atoms, and epoxidized products of unsaturated fatty acids having 12 to 18 carbon atoms and an alcohol having 20 or less carbon atoms is more preferable. These plasticizers have improved compatibility with the acrylic copolymer containing 10% by mass or more of one or more monomers selected from the above-mentioned dodecyl (meth)acrylate and tridecyl (meth)acrylate, and can suppress contamination of the adherend under high temperature and high humidity conditions.

[0038] Examples of saturated fatty acids having 12 to 18 carbon atoms include lauric acid, myristic acid, palmitic acid, stearic acid, isopalmitic acid, isostearic acid, etc. Examples of unsaturated fatty acids having 12 to 18 carbon atoms include palmitoleic acid, oleic acid, linoleic acid, etc. Furthermore, epoxidized products of unsaturated fatty acids having 12 to 18 carbon atoms are products in which the unsaturated site of the unsaturated fatty acid is epoxidized with a peroxide or the like. The epoxidized products may be products obtained by dehydration condensation of unsaturated fatty acids and alcohols, followed by epoxidization. The above-mentioned saturated fatty acids, unsaturated fatty acids and epoxidized products may be used alone or in combination of two or more. Examples of the combination of two or more include vegetable oils, such as soybean oil and linseed oil.

[0039] Examples of ester compounds of saturated fatty acids having 12 to 18 carbon atoms, unsaturated fatty acids having 12 to 18 carbon atoms, and epoxidized unsaturated fatty acids having 12 to 18 carbon atoms with alcohols having 20 or less carbon atoms include methyl laurate, isopropyl myristate, isopropyl palmitate, methyl oleate, octyldodecyl oleate, epoxidized soybean fatty acid butyl, and epoxidized linseed fatty acid butyl.

[0040] The plasticizer is preferably contained in an amount of 0.1 parts by mass or more, more preferably 1 part by mass or more, and even more preferably 3 parts by mass or more, based on 100 parts by mass of the acrylic copolymer. The amount is preferably 30 parts by mass or less, more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less. By keeping the amount within the above range, the removability is improved and the adhesive strength to the oily surface is maintained.

[0041] <Other ingredients> The adhesive composition may contain other components as necessary within the scope of the effects of the present invention. Examples of other components include curing agents, solvents, silane coupling agents, heat or light stabilizers, UV absorbers, leveling agents, defoamers, antibacterial agents, moisturizers, vitamins, pigments, dyes, fragrances, tackifier resins, etc. These can be appropriately selected from known ones and used.

[0042] (hardening agent) The adhesive composition may contain a curing agent. In the adhesive composition, the curing agent is mainly used to crosslink the acrylic copolymer. Crosslinking by the curing agent improves the heat resistance, chemical stability, and adhesive strength of the adhesive composition. Examples of the curing agent include epoxy-based curing agents, isocyanate-based curing agents, chelate-based curing agents, and aziridines, and these may be used alone or in combination of two or more. The curing agent is preferably an epoxy-based curing agent or an isocyanate-based curing agent, since it gives a composition having good adhesive strength with a small difference between the adhesive strength to an oily surface and the adhesive strength to a non-oily surface, and is also excellent in heat resistance.

[0043] The epoxy-based curing agent mainly reacts with the carboxyl group of the acrylic copolymer to crosslink the acrylic copolymers. The epoxy-based curing agent may be appropriately selected from compounds having two or more epoxy groups in one molecule according to the physical properties required for the adhesive layer. Specific examples of epoxy curing agents include chain polyfunctional epoxy compounds such as ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, 1,6-hexanediol diglycidyl ether, and trimethylolpropane triglycidyl ether; Examples of epoxy compounds having a ring structure include 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, glycerin triglycidyl ether, triglycidyl isocyanurate, N,N,N',N'-tetraglycidyl-m-xylylenediamine, N-diglycidylaniline, N,N,N',N'-tetraglycidylaminophenylmethane, mN,N-diglycidylaminophenylglycidyl ether, and N,N-diglycidyltoluidine. From the viewpoint of heat resistance, epoxy compounds having a ring structure are preferred, and from the viewpoint of curing speed, compounds containing a nitrogen atom in the molecule are preferred. The epoxy curing agents can be used alone or in combination of two or more.

[0044] Examples of the isocyanate curing agent include adducts of isocyanate monomers, such as tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethylxylylene diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenyl isocyanate, with polyol compounds, such as trimethylolpropane; biuret products of the isocyanate monomers; isocyanurate products of the isocyanate monomers; and compounds having three or more isocyanate groups in the molecule, such as adducts of the isocyanate monomers and known polyether polyols or polyester polyols, acrylic polyols, polybutadiene polyols, polyisoprene polyols, and the like. Examples of the isocyanate monomer include tolylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, tetramethylxylylene diisocyanate, naphthalene diisocyanate, triphenylmethane triisocyanate, and polymethylene polyphenyl isocyanate; and compounds having two isocyanate groups in the molecule, such as an allophanate of hexamethylene diisocyanate (Coronate 2770: manufactured by Nippon Polyurethane Industry Co., Ltd.). Among these, a trimethylolpropane adduct of tolylene diisocyanate is preferred because it can easily adjust the adhesive properties. The number of isocyanate groups is the average number.

[0045] When a curing agent is used, the content of the curing agent in the adhesive composition is preferably 0.005 to 15 mass%, more preferably 0.01 to 10 mass%, even more preferably 0.02 to 5 mass%, and particularly preferably 0.03 to 4 mass%, relative to 100 parts by mass of the acrylic copolymer, since a composition having good adhesive strength with a small difference between the adhesive strength to an oily surface and the adhesive strength to a non-oily surface can be obtained.

[0046] (solvent) The adhesive composition may contain a curing agent. The solvent can be appropriately selected from those that have low reactivity with each component constituting the adhesive composition and can dissolve or disperse each component, taking into consideration the coatability and the like. Specific examples of suitable solvents include hydrocarbon solvents such as toluene, xylene, hexane, and heptane; ester solvents such as ethyl acetate and butyl acetate; ketone solvents such as acetone and methyl ethyl ketone; halogenated hydrocarbon solvents such as dichloromethane and chloroform; ether solvents such as diethyl ether, methoxytoluene, and dioxane, and other hydrocarbon solvents. The solvents may be used alone or in combination of two or more.

[0047] [Adhesive sheet] The adhesive sheet according to the present invention (hereinafter, also referred to as the present adhesive sheet) comprises an adhesive layer containing the present adhesive composition or a cured product thereof on a substrate. The adhesive sheet can be produced, for example, by applying an adhesive to a substrate, drying the adhesive, and curing the adhesive as necessary. The adhesive layer may be provided on at least one surface of the substrate.

[0048] When applying the adhesive composition, the viscosity may be adjusted by adding the solvent, or the viscosity of the adhesive composition may be reduced by heating.

[0049] Examples of the substrate include cellophane, plastic sheets, rubber, foams, fabrics, rubber fabrics, resin-impregnated fabrics, glass plates, and wood, and may be in the form of a plate or a film. The substrate may be used alone or may be a laminate of a plurality of substrates. The substrate may have a release-treated surface (hereinafter, referred to as a release sheet).

[0050] Examples of plastic sheets (also called plastic films) include polyvinyl alcohol films, triacetyl cellulose films, polyolefin resin films such as polypropylene, polyethylene, polycycloolefin, and ethylene-vinyl acetate copolymers, polyester resin films such as polyethylene terephthalate, polybutylene terephthalate, and polyethylene naphthalate, polycarbonate resin films, polynorbornene resin films, polyarylate resin films, acrylic resin films, polyphenylene sulfide resin films, polystyrene resin films, vinyl resin films, polyamide resin films, polyimide resin films, and epoxy resin films.

[0051] In the present invention, the method of applying the adhesive composition is not particularly limited, and examples thereof include a Mayer bar, an applicator, a brush, a spray, a roller, a gravure coater, a die coater, a lip coater, a comma coater, a knife coater, a reverse coater, and a spin coater. The drying method is not particularly limited, and examples thereof include hot air drying, infrared rays, and a reduced pressure method. Drying conditions vary depending on the curing form of the adhesive, the film thickness, and the selected solvent, but hot air heating at about 60 to 130°C is usually sufficient.

[0052] The adhesive sheet of the present invention can be obtained by (a) coating an adhesive composition on the release-treated surface of a release-treated film, drying it, and laminating a substrate on the surface of the adhesive layer, or by (b) directly coating an adhesive composition on a substrate, drying it, and laminating the release-treated surface of a release-treated film on the surface of the adhesive layer.

[0053] The thickness of the adhesive layer is preferably 0.1 to 300 μm, more preferably 1 to 200 μm, and further preferably 3 to 150 μm. EXAMPLES

[0054] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to these examples. The blending ratios are expressed in terms of solid content except for the solvent. In addition, "parts" refers to "parts by mass."

[0055] (Synthesis Example 1) A reaction vessel (hereinafter simply referred to as "reaction vessel") equipped with a stirrer, a thermometer, a reflux condenser, a dropping device, and a nitrogen inlet tube was charged with 96.5 parts of dodecyl methacrylate, 3 parts of acrylic acid, 0.5 parts of hydroxyethyl acrylate, 67 parts of ethyl acetate, and 0.04 parts of benzoyl peroxide (BPO), and the air in the reaction vessel was replaced with nitrogen gas. Next, the mixture was heated to 80°C while stirring under a nitrogen atmosphere to start the reaction. Furthermore, an equal amount of the mixture charged in the reaction vessel was charged into a dropping funnel, dropped, and a polymerization reaction was carried out at the reflux temperature under a nitrogen atmosphere for 7 hours. After the reaction was completed, the mixture was cooled and diluted with ethyl acetate to obtain a copolymer solution with a non-volatile content of 45% and a viscosity of 3000 mPa·s. The weight average molecular weight (Mw) of the obtained copolymer was measured by the following method, and was found to be 720,000. The obtained copolymer is designated as copolymer (A-1).

[0056] (Synthesis Examples 2 to 17) Acrylic copolymers were synthesized in the same manner as in Synthesis Example 1, except that the types and blending ratios of the monomers in Synthesis Example 1 were changed as shown in Table 1. The obtained copolymers are referred to as copolymers (A-2) to (A-17), in this order.

[0057] (Synthesis Examples 18-20: Comparative Synthesis Examples) Acrylic copolymers were synthesized in the same manner as in Synthesis Example 1, except that the types and blending ratios of the monomers in Synthesis Example 1 were changed as shown in Table 1. The obtained copolymers are referred to as copolymers (A-18X) to (A-20X), in that order.

[0058] <Measurement of weight average molecular weight (Mw)> The Mw of each copolymer was measured under the following conditions: Mw was determined by a calibration curve method using polystyrene with a known weight average molecular weight as the standard substance. Device name: Shimadzu Corporation, LC-GPC system "Prominence" Column: 4 Tosoh GMHXL columns and 1 Tosoh HXL-H column connected in series Mobile phase solvent: Tetrahydrofuran (THF) Flow rate: 1.0ml / min Column temperature: 40℃

[0059] [Table 1]

[0060] The abbreviations in Table 1 are as follows: DA: Dodecyl acrylate DMA: Dodecyl methacrylate TDA: Tridecyl acrylate TDMA: Tridecyl methacrylate 2EHA: 2-Ethylhexyl acrylate AA: Acrylic acid HEA: Hydroxyethyl acrylate SA: Stearyl acrylate

[0061] (Example 1) <Preparation of Adhesive Composition> The adhesive composition of Example 1 was obtained by mixing and stirring 100 parts of the acrylic copolymer (A-1), 3 parts of the plasticizer IPP, 2.5 parts of the curing agent TDI-TMP adduct, and ethyl acetate as a dilution solvent.

[0062] <Creating adhesive sheets> The adhesive composition of Example 1 was applied to a 38 μm thick polyester separator [trade name "Superstic" SP-PET38, manufactured by Lintec Corporation, the same applies below] so that the thickness after drying would be 50 μm, and the adhesive layer was formed by drying in a hot air oven at 100° C. for 2 minutes. After drying, the adhesive layer was laminated to a 25 μm thick polyethylene naphthalate (PEN) film (Teonex, manufactured by Teijin Co., Ltd.), and further aged at 23° C. and 50% RH for 7 days to obtain the adhesive sheet of Example 1.

[0063] (Examples 2 to 33) Adhesive compositions and adhesive sheets were obtained in the same manner as in Example 1, except that the types and blending ratios of the acrylic copolymer, plasticizer, curing agent and solvent in Example 1 were changed as shown in Table 2. Examples 1 to 29 are working examples, and Examples 30 to 33 are comparative examples.

[0064] [evaluation] <Adhesive strength evaluation> The pressure-sensitive adhesive sheet of each example was cut to a size of 25 mm wide and 100 mm long. Next, in an environment of 23°C and 50% RH, the separator was peeled off from the pressure-sensitive adhesive sheet, and the exposed pressure-sensitive adhesive layer was attached to the following adhesion surfaces 1 and 2, respectively, and rolled back and forth once with a 2 kg roll to prepare a measurement sample. After storing this measurement sample in an environment of 23°C and 50% RH for 24 hours, the peel strength was determined using a tensile tester (Orientec Co., Ltd.'s "Tensilon") at a peel speed of 300 mm / min and a peel angle of 180°. The non-oily surface was evaluated by peel strength, and the oily surface was evaluated based on the ratio (A / B) of peel strength A of the oily surface to peel strength B of the non-oily surface, according to the following evaluation criteria. The results are shown in Table 2. (Surface to be adhered to) Adhesion surface 1: Stainless steel (SUS) plate with no oil applied (non-oily surface) Adhesion surface 2: Canola oil, Nisshin Oillio (edible oil) applied to the surface at 4g / m 2 Stainless steel plate evenly coated with

[0065] (Adhesive strength evaluation criteria) (1) Evaluation of unoiled stainless steel plate ⊚: The peel strength was 4N / 25mm or more and less than 8N / 25mm (very good). ◯: The peel strength was 3 N / 25 mm or more and less than 10 N / 25 mm, except for the range of 4 N / 25 mm or more and less than 8 N / 25 mm (good). △: The peel strength was 1N / 25mm or more and less than 15N / 25mm, except for the range of 3N / 25mm or more and less than 10N / 25mm (usable). ×: The peel strength was 0 N / 25 mm or more and less than 20 N / 25 mm, except for the range of 1 N / 25 mm or more and less than 15 N / 25 mm (unusable). (2) Evaluation of oil-coated stainless steel plate ⊚: The peel strength was 80% or more and 120% or less of that of a non-oily surface (very good). ◯: The peel strength was 60% or more and less than 80% of that of a non-oily surface (good). △: The peel strength was 40% or more and less than 60% of that of a non-oily surface (usable). ×: The peel strength was less than 40% of that of the non-oily surface (unusable).

[0066] <Removability evaluation> The pressure-sensitive adhesive sheet of each example was cut to a size of 25 mm in width and 100 mm in length. Next, in an environment of 23°C and 50% RH, the separator was peeled off from the pressure-sensitive adhesive sheet, and the exposed pressure-sensitive adhesive layer was attached to each of the following adhesion surfaces 1 to 6, and rolled back and forth once with a 2 kg roll to prepare a measurement sample. The measurement samples were stored for 7 days in an environment of 60°C / 95% RH or 80°C / 95%, and then peeled at a peel speed of 300 mm / min and a peel angle of 180° using a tensile tester (Orientec Co., Ltd.'s "Tensilon"), and the condition of the adherends after peeling was observed. The results are shown in Table 2. (Removability evaluation criteria) : No contamination on the adherend (very good). ◯: Slight cloudiness observed on the adherend (good). △: Cloudiness is observed on the substrate (usable). ×: Adhesive is attached to the adherend (unusable).

[0067] <Retention strength evaluation> Adhesive sheets for each example were prepared measuring 25mm wide x 150mm long. The release sheet was removed from the adhesive sheet, and the adhesive layer was attached to a 25mm wide x 25mm long section of the bottom edge of a polished stainless steel plate measuring 30mm wide x 150mm long. The adhesive was then pressed back and forth once with a 2kg roll, after which a load of 1kg was applied in an atmosphere of 40℃ or 80℃ and the sheet was left for 70,000 seconds to measure the holding power. The length by which the top edge of the adhesive sheet surface shifted downward was measured for evaluation. The results are shown in Table 2.

[0068] (Retention strength evaluation criteria) ◎: 0 mm / 70,000 seconds (very good). ○: Over 0 mm and less than 3.0 mm / 70,000 seconds (good). △: Over 3mm and less than 25.0mm / 70,000 seconds (usable). ×: Fallen (over 25.0 mm) (unusable).

[0069] [Table 2]

[0070] The abbreviations in Table 2 are as follows: TDI-TMP: Trimethylolpropane adduct of tolylene diisocyanate TDS: Isotridecyl stearate IPP: Isopropyl palmitate IPM: Isopropyl myristate ML: Methyl laurate MOL: Methyl oleate BES: Epoxidized butyl soyate ATBC: Acetyl tributyl citrate EHT: 2-Ethylhexyl trimellitate DOA: Dioctyl adipate DOP: Dioctyl phthalate

[0071] [Summary of results] As shown in Table 2, it was revealed that the adhesive sheets obtained using the adhesive compositions of Examples 1 to 29, which contain an acrylic copolymer containing 10 mass% or more of C12-13 alkyl (meth)acrylate and a plasticizer, have good adhesive strength, and the difference in adhesive strength between an oily surface and a non-oily surface is small.

Claims

1. A pressure-sensitive adhesive composition comprising an acrylic copolymer, a plasticizer, a curing agent, and a solvent, the acrylic copolymer containing 10% by mass or more of one or more monomers selected from dodecyl (meth)acrylate and tridecyl (meth)acrylate, A copolymer containing 1 to 20% by mass of a monomer having a carboxyl group, The adhesive composition, wherein the plasticizer comprises an ester compound derived from one or more selected from a saturated fatty acid having 12 to 18 carbon atoms, an unsaturated fatty acid having 12 to 18 carbon atoms, and an epoxidized product of an unsaturated fatty acid having 12 to 18 carbon atoms.

2. The pressure-sensitive adhesive composition according to claim 1 , wherein the acrylic copolymer is a copolymer containing 80 mass % or more of one or more monomers selected from dodecyl (meth)acrylate and tridecyl (meth)acrylate.

3. The pressure-sensitive adhesive composition according to claim 1 or 2, wherein the plasticizer comprises an ester compound of one or more selected from a saturated fatty acid having 12 to 18 carbon atoms, an unsaturated fatty acid having 12 to 18 carbon atoms, and an epoxidized product of an unsaturated fatty acid having 12 to 18 carbon atoms, and an alcohol having 20 or less carbon atoms.

4. The pressure-sensitive adhesive composition according to any one of claims 1 to 3, wherein the acrylic copolymer further contains a monomer having a hydroxyl group.

5. A pressure-sensitive adhesive sheet comprising a substrate and a pressure-sensitive adhesive layer comprising the pressure-sensitive adhesive composition according to any one of claims 1 to 4 or a cured product thereof.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive tape or sheet

    JP1991292379A

  • Prevention of ultraviolet deterioration of tacky agent

    JP2000063786A

  • Emulsion type adhesive composition

    JP2000313863A

  • Strap

    JP2003081817A

  • Photopolymerizable adhesive composition, and adhesive sheet using the same

    JP2012072406A